The text El ser sobrenatural as an indispensable context for understanding epistemology, metaphysics and the vision of God in the philosophy by Xavier Zubiri - Niziński, Rafał S. (Filozofia Chrześcijańska, 2021)
The philosophy of Xavier Zubiri is recognized as one of the most diffi cult to understand because there is something unclear in it. Therefore one may guess that there is a hidden presumption done by Zubiri. Zubiri in the self-presentation of his philosophical backgrounds acknowledges that his philosophy owes most to the phenomenology of Husserl and metaphysics of Heidegger. He also admits of being infl uenced by Aristotle to a certain degree. Zubiri starts his analyses from perception of things, with which he fulfi lls phenomenological requirement of beginning philosophy with the description of reality. As the fi nal step he ads metaphysics, which explains the description of reality. Following this code of interpretation of Zubiri’s philosophy it is difficult to grasp its core meaning. What is this hidden supposition? In The Supernatural Being: God and Deifi cation in Saint Paul’s Theology, which he wrote in the 30s’ and 40s’ of the 20th century, Zubiri presents early Christian Neoplatonic theology. In the same work Zubiri also states that it is possible to discover the same ideas following the way up, i.e. departing from the creatures and ascending to God. And this will be the hidden supposition of his philosophy. This paper tries to show the philosophy of Zubiri can be understood as a kind of proof that the Neoplatonic vision of the reality presented in The Supernatural Being: God and Deifi cation in Saint Paul’s Theology is true and can be discovered by reason alone, i.e. departing only from description of facts.